2014
DOI: 10.1016/j.fsigen.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative European exercise on mRNA-based body fluid/skin typing and interpretation of DNA and RNA results

Abstract: The European Forensic Genetics Network of Excellence (EUROFORGEN-NoE) undertook a collaborative project on mRNA-based body fluid/skin typing and the interpretation of the resulting RNA and DNA data. Although both body fluids and skin are composed of a variety of cell types with different functions and gene expression profiles, we refer to the procedure as 'cell type inference'. Nine laboratories participated in the project and used a 20-marker multiplex to analyse samples that were centrally prepared and thoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 32 publications
3
43
0
3
Order By: Relevance
“…The use of RT-PCR to detect mRNA transcripts has shown that inconsistent results can be observed and explained as 'sporadic' in some studies [38]. To help explain these findings, we used MPS data from fresh and degraded body fluids mapped against the human reference genome (hg19) to deliberately design primers for mRNA regions in which higher read counts were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of RT-PCR to detect mRNA transcripts has shown that inconsistent results can be observed and explained as 'sporadic' in some studies [38]. To help explain these findings, we used MPS data from fresh and degraded body fluids mapped against the human reference genome (hg19) to deliberately design primers for mRNA regions in which higher read counts were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Further testing was undertaken to assess the reproducibility of target detection using StaR primers, as the inconsistency of RNA marker detection could be problematic in forensic body fluid identification [38]. Replicate amplifications using conventional HTN3, UBE2D2, and SLC4A1 primers resulted in irregular (or inconsistent) target amplification and some replicates failed to generate amplicons (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Forensics, there has been an increase in interest for RNA studies. Out of the several fields of application , the tissue‐specific gene expression of RNA makes this molecule the ideal tool for determining the cellular origin of unknown samples . In addition, most recently, tissue‐specific transcriptional changes were described as a response to the death of the human organism, thus opening the frontiers to a molecular evaluation of the postmortem interval .…”
Section: Introductionmentioning
confidence: 99%
“…For example, current techniques would not normally distinguish venous from menstrual blood. While both would give positive reactions using presumptive chemical tests, even tissue-specific mRNA typing could still raise doubts about the origin, mainly due to the co-existence of blood peaks when menstrual blood is present [23,24]. In DNA methylation-based studies in forensic identification for blood, potential markers such as cg06379435 [25,26], cg08792630 [26], cg26285698 [12], cg04011671 and cg18454288 [14] have been identified through genome-wide methylation arrays, such as the Illumina Human Methylation 450K bead array.…”
Section: Introductionmentioning
confidence: 99%